Investigation of energy confinement during ICRF heating on EAST. (28th June 2017) - Yang, Y Q; Zhang, X J; Zhao, Y P; Qin, C M; Cheng, Y; Mao, Y Z; Yang, H; Yuan, S; Wang, L; Ju, S Q; Chen, G; Zhang, J H; et al.
Abstract: A summary is given on recent experiments in L-mode with ion cyclotron resonance heating (ICRH) of hydrogen minority in deuterium plasmas on EAST. Experiments show a degradation of confinement with increasing power. Furthermore, the energy confinement time increases with plasma current and magnetic field, whereas it is insensitive to line averaged density. Minority heating has been found to be efficient, and parameters were optimized to maximize its efficiency. ICRH in lower hybrid waves heated plasma was also investigated.